The Implications of Dörnyei’s Foreign Language Learning Motivation Theory for Chinese Language Teaching in Korea - Kanghoon, Lim (Journal of Maobi, 2025)
Motivation is a core construct in second and foreign language acquisition research. Over the past five decades, it has evolved from a peripheral psychological variable to one of the most decisive factors determining success in language learning. This paper revisits Zoltán Dörnyei’s influential theory of foreign-language learning motivation, tracing its intellectual roots from Gardner and Lambert’s socio-educational model to contemporary perspectives such as the L2 Motivational Self System. Within the specific context of Chinese language education in Korea a rapidly growing but pedagogically complex domain the paper explores how motivational theories can inform curriculum design, classroom practice, and teacher professional development. It argues that understanding learners’ motivational patterns is essential for creating sustainable engagement, especially in contexts where instrumental goals initially dominate. By synthesizing existing research and integrating illustrative classroom examples, the paper proposes a comprehensive motivational framework for teaching Chinese in Korea. This framework incorporates linguistic, psychological, and sociocultural dimensions, highlighting the dynamic interplay between learners’ self-systems, teacher behavior, and educational environment. Ultimately, the study aims to contribute to the theoretical localization of Dörnyei’s model in East Asian Chinese-language education and to offer practical insights for motivating Korean learners in both traditional and technology-enhanced classrooms.